Współdzielenie i współodczuwanie zamiast osądzania. Duchowe wsparcie sztuki w zakonach i laickich wspólnotach żeńskich Kalifornii - Markowska, Anna (Artium Quaestiones, 2024)
California’s feminist art of the counterculture era thrived in both women’s religious and secular communities, ranging from the Convent of the Sisters of the Immaculate Heart of Mary to art collectives established at universities. During the historical transition from high modernism to emerging postmodernism, collective affirmative strategies emerged, renewing the debate between religion and the public sphere. These transformative practices of post-secular affirmativeness fostered a renewed relationship with the Goddess and a close connection between art and life. Engaging with the work on a personal level changed the role of the art historian, moving away from focusing solely on the autonomy and formal aspects of the artwork. The dignity of female artists and participants in artistic activities required the art historian to approach their work with empathy and respect, understanding their motivations. The task then became to develop an empathetic language of mediation in the public space, even for works deemed blasphemous or outside accepted norms. Movements like feminism, womanism, and mujerista demand that art historians consider art in conjunction with the women it helps, rather than in isolation. The shift in how artwork and the role of the art historian are perceived is evident when adopting a post-secular perspective. The key terms used to analyze the art of female artists from California are feminism and postsecularism. Feminism, as defined by Giselle Vincett, involves deconstructing traditionalism, merging Christianity with other forms of spirituality, and reimagining the divine consistent with feminist values. Post-secularism, according to Rosi Braidotti, entails renewing the debate between religion and the public sphere enabling the search for creative, inclusive future scenarios. Artists seeking spiritual support in their work, during what Andrew Blauvelt termed the era of “hippie modernism,” promoted concepts that emerging postmodernism found unacceptable: grand narratives, all-unity, and essentialism. They also ignored the modernist religious-secular binary. These artists made sense of their work and lives through a positive vision of sisterhood and the belief that religion and spirituality can intensify collective life and inspire individual achievements. The article does not dichotomize between female artists working in traditional religious communities and those in secular collectives. In addition to discussing the work of Sr. Corita Kent, who captures the language of advertising, it explores the work of Ester Hernández, who transforms the traditional iconography of Our Lady of Guadalupe. It also examines Linda Montano, who speaks in the voice of St. Teresa of Ávila, among others; Barbara Smith, who establishes the religion of the Holy Squash; and Judy Chicago, who creates a work reminiscent of a female Last Supper with a group of women.